Histopathological Review on Discoid Lupus Erythematous Mimicking Granuloma Faciale - Putti Fatiharani Dewi; Fiska Rosita; Triasari Oktavriana; Ambar Mudigdo (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Discoid lupus erythematosus is the most common forms of chronic cutaneous lupus erythematosus. It is characterized by clinical manifestations of erythematous macules, papules, or plaques with a coin-like shape and the face is the most common predilection site. Clinical features often resemble granuloma faciale. This case report aimed to distinguish discoid lesions on the face based on the histopathological examination. A 71-year-old male with a few reddish lumps appeared on his face since three months ago. Physical examination showed multiple discrete erythematous plaques with overlying squamous. Hematoxylin and eosin staining on the epidermis demonstrated basket weave type orthokeratosis, basal vacuolar cell degeneration, epidermal atrophy with flat rete ridges, and follicular plugging while in the dermis obtained inflammatory cell infiltrates, especially in periadnexal areas. Histopathological features of DLE are hyperkeratosis, pilosebasea gland atrophy, follicular plugging, basal membrane thickening, and cellular infiltrate in periadnexa or perivascular areas more visible than in other types of CLE. In DLE, no subepidermal gren zone and eosinophil infiltrate were found, like histological features of granuloma faciale. Histopathological examination can be used to establish a diagnosis for discoid lesions on the face, although serology examination remains as the gold standart. Keywords:  Discoid lupus erythematosus; Granuloma faciale; Histopathology